Functional Browlifting - Dunn, Brandyn S.; Humphrey, Clinton D.; Kriet, J. David (Facial Plastic Surgery, 2022)
Brow ptosis is an abnormal descent of the eyebrow resulting in a displeased appearance and/or functional deficit. While most cases of brow ptosis do not result in a functional impairment, functional brow surgery is generally reserved for individuals with severe brow asymmetry or visual field deficit related to excess soft tissue pushing downward on the eyelid. A combination of both intrinsic and extrinsic anatomic factors contributes to an unfavorable brow shape, contour, and position. Proper management of brow ptosis requires an understanding of both surgical and nonsurgical modalities. Traditionally, individuals with functional brow ptosis are treated by browpexy via blepharoplasty approach, direct browlift, mid-forehead browlift, or less commonly endoscopic browlift.
Keywords: browlift; functional browlift; brow ptosis; mid-forehead browlift; direct browlift; facial paralysis